External Beam Radiotherapy for Dysphagia Palliation in Advanced Esophageal Cancer: A Prospective Study - Das, Abhinandan; Kalita, Apurba Kumar; Bhattacharyya, Mouchumee; Nath, Jyotiman; Yanthan, Yanpothung; Das, Tapashi; Das, Ankita; Neog, Moniprom; Sonar, Mongal (Asian Pacific Journal of Cancer Care, 2023)
Background and Objective: Esophageal cancer is a highly aggressive malignancy often associated with a poor prognosis due to locoregional failure and distant metastases. Approximately 60–70% of patients present at an advanced stage, with a median survival of 6-10 months and are not candidates for definitive treatment. Dysphagia is the most common symptom, affecting 80%–90% of patients. The primary goal in managing patients with advanced disease is dysphagia control, which can improve nutritional intake and quality of life. External beam radiotherapy (EBRT) is a major palliative treatment option. The primary objective of this study was to assess the efficacy of external beam radiotherapy in alleviating dysphagia in patients with esophageal cancer. Materials and Methods: This single-arm prospective clinical study was conducted at a tertiary care hospital in Northeast India. The study included 57 esophageal cancer patients ineligible for definitive treatment. Patients received EBRT of 30 Gy in 10 fractions over two weeks. Dysphagia was graded using the Modified Takita's grading system. Patients were followed up at one-month intervals after treatment to assess dysphagia and acute toxicity. Results: Among 57 patients in the study, subjective dysphagia relief was observed in 82.45%. The median dysphagia score decreased from 3 to 2 at the end of the 3-month post-treatment period (p < .001). In terms of treatment-related toxicity, the treatment was well-tolerated. No grade 4-5 toxicity was encountered. The most common toxicity was radiation esophagitis, affecting 15 patients (26.31%). Conclusion: Radiation can significantly improve dysphagia in esophageal cancer patients. It is suggested as an effective, non-invasive, and well-tolerated method for treating dysphagia in selected individuals with incurable esophageal cancer.